The international humanitarian law classification of armed conflicts in Iraq since 2003 - Turns, David (Naval War College Newport, Rhode Island, 2010)
An armed conflict, within the meaning of international humanitarian law (IHL), began in Iraq when that country was invaded by military forces of the coalition composed primarily of the United States, the United Kingdom and Australia in March 2003. It continues to this day, notwithstanding a certain decline in intensity since the British withdrawal in July 2009 and the reorganization of US forces under a new security agreement with the Iraqi government in December of the same year.